Bone-Marrow Derived Dendritic Cells From Toxoplasma Gondii Chronically Infected Mice Exhibit Alterations In Monoclonal And Polyclonal T Cell Priming - Perrone Sibilia, Matias (2021)
Rationale: We previously showed that splenocytes from chronic T. gondii infected mice have a diminished capacity to activate and differentiate OVA-specific Th1 and Th2 cells. Moreover, BMDCs from infected animals presented phenotypic alterations as shown by increases in CD80 and CD86 maturation markers and fewer secretion levels of IL-6 and IL-10, with no differences in IL-12. To extend these previous results, herein, we studied the ability of BMDC from chronically infected mice to activate and differentiate effector T cells. Methods: Bone-marrow derived dendritic cells (BMDCs) were obtained from naive and chronically infected mice, by culturing bone-marrow precursors for nine days with GM-CSF-conditioned medium. Afterward, BMDC were fed with OVA and matured during 18h with LPS. Subsequently, BMDC were cultured with DO11.10 OVA-specific CD4+T cells. Also, a mixed lymphocyte reaction (MLR) was performed by co-culturing BMDC with naive C57BL/6 mice splenocytes. Results: OVA specific CD4+ T cells co-cultured with BMDCs from infected mice showed lower levels of IFN-γ and IL-5 and increased levels of IL-10 (p<0.05). When analyzing polyclonal T cell responses in MLR assays, T lymphocytes incubated with BMDCs from infected mice showed decreased secretion of IFN-γ and IL-10 (p<0.01). No significant differences were observed for Th2 cytokines. Conclusion: The data obtained with BMDCs show that mice chronically infected with T. gondii present alterations of bone-marrow precursors. Interestingly, the diminished Th1/Th2 profiles observed in antigen specific co-culture assays are in line with results previously observed in splenocytes from T. gondii infected mice. These results suggest that infection with T. gondii results in long-lasting alterations in hematopoietic cells that could be involved in the lower susceptibility to developing allergic and autoimmune disorders.